Vortex lattice mobility and effective pinning potentials in the peak effect region in YBCO crystals - Pasquini, Gabriela (2006)
The peak effect (PE) in the critical current density in both low and high temperature superconductors has been the subject of a large amount of experimental and theoretical work in the last few/several years. In the case of YBCO, crucial discussions describing a, dynamic or a, static picture are not settled. In that region of field and temperature the mobility of the vortex lattice (VL) is found to be dependent on the dynamical history. Recently we reported evidence that the VL reorganizes and accesses to robust VL configurations (VLCs) with different effective pinning potential wells arising in response to different system histories. One of the keys to understand the nature of the PE is to investigate the VL behavior in the vicinity of the various VLCs in the region of the PE. The stability of these VLCs was investigated and it was found that they have distinct characteristic relaxation times, which may be related to elastic or plastic creep processes. In this paper we review some of these results and propose a scenario to describe the PE in YBCO crystals. © Indian Academy of Sciences.